2018
DOI: 10.1007/s10384-018-0585-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of fusional convergence amplitude in postoperative phoria maintenance in children with intermittent exotropia

Abstract: In childhood X(T), fusional amplitude plays a role in enforcing the patient's ability to maintain phoria. However, sufficient fusional amplitude does not guarantee fully functioning fusion if suppression is present during phoria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Scholars performed two methods and reported that the stereopsis of patients with intermittent exotropia after operation increased [22]. Li Dan et al have surveyed different types of intermittent exotropia and indicated that surgery is helpful to the recovery of binocular regulatory set function [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars performed two methods and reported that the stereopsis of patients with intermittent exotropia after operation increased [22]. Li Dan et al have surveyed different types of intermittent exotropia and indicated that surgery is helpful to the recovery of binocular regulatory set function [23].…”
Section: Discussionmentioning
confidence: 99%
“…Scholars performed two methods and reported that the stereopsis of patients with intermittent exotropia after operation increased [ 22 ]. Li Dan et al have surveyed different types of intermittent exotropia and indicated that surgery is helpful to the recovery of binocular regulatory set function [ 23 ]. The clinical study of binocular visual function in children with intermittent exotropia before and after operation suggests that surgical therapeutics is beneficial to the reconstruction of binocular visual function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fusional vergence amplitude reflects a patient’s ability to “control” a latent or intermittent deviation in IXT ( von Noorden and Campos, 2002 ; Adams et al, 2008 ) or a patient’s ability to maintain phoria in childhood X(T) ( Wakayama et al, 2018 ). Kushner and Morton (1998) and Kushner (1999) found that exotropia becomes more pronounced when fusional convergence is suspended.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has limitations. First, the control score plays a vital role in assessing the patients’ ability to maintain phoria ( Hatt and Gnanaraj, 2013 ; Wakayama et al, 2018 ). However, it is unsuitable for patients with IXT after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Given their differences from normal children, binocular vision is more critical for children with IXT, as if these individuals lose maintenance of fusion, they could manifest exotropia. Previous studies proved that the positive fusional vergence (PFV) and fusion reserve ratio were correlated with the ability to maintain ocular alignment [13][14][15], and PFV was lower in IXT than in visually normal children [16,17], which could make it difficult for the fusional maintenance system to control ocular deviation. Since contact lenses for myopia control may influence the vergence and fusion systems in normal myopic children [8][9][10], therefore, it is worth exploring whether specialized spectacle lenses for myopia control will also affect binocular vision in myopic children, especially those with IXT.…”
Section: Introductionmentioning
confidence: 99%